PENGARUH KENAIKAN HARGA BAHAN BAKAR MINYAK TERHADAP TARIF ANGKUTAN UMUM (Studi Kasus : Angkot Trayek Tobelo -Tobelo Utara) - Sintia Talimbo, Friska; Hi. Posi, Sahrul; Manoma, Suharli (CV. Anugerah Duta Perdana, 2024)
The purpose of this study was to determine the effect of rising fuel prices on public transport fares in Tobelo City, specifically the North Tobelo-Tobelo Route. The sample in this study amounted to 40 people. Based on the research results it is known that the tcount value of 3.600 is greater than the ttable which is equal to 2.024 and it can be seen that the significance value of 0.001 is less than 0.05, which means that the price of fuel oil (BBM) greatly determines the fare on public transportation. While the determinant coefficient (R2) that the strength of the relationship between the increase in fuel prices and the increase in public transport fares is quite strong or equal to 50.4%. While the determinant coefficient (R2) obtained an adjusted R-square value of 0.254 or 25.4%. This means that the increase in public transport fares is influenced by the variable contribution of the fuel price increase by 25.4% while the remaining 74.6% (100% -25.4%) is influenced by other variables not explained in this study.